Self-assembled Fe nanodots on Ge (001) - SHVETS, IGOR (My University, 2006)
The initial nucleation of Fe onto the (2x1) reconstructed Ge(001) surface is studied. Uniformly sized two-dimensional Fe dots are shown to nucleate. They have an apparent corrugation height similar to 1.1 A and lateral dimensions similar to 12x8 A(2). Further to their uniform size, due to their registry with respect to the substrate, they are shown to nucleate on a single equivalent surface site. It is suggested that their stability is due to either a "magic" number effect or adsorbate-substrate interactions. Tunneling I(V) spectra show the dot/Ge(001) contact to exhibit marked current rectifying behavior, which is extremely well confined to the contact area.
PUBLISHED
Keywords: self-assembly; Fe; nanodots; Ge(001); surface; nanostructures; clusters; Si(111)-(7x7); Nanoscience & Materials